COPING STRATEGIES AND RESILIENCE AS MEDIATING FACTORS OF GRIEF FOR THE LOSS OF HEALTH - González Toledo, Jessenia Ivanova (2025)
Introduction: The most frequently diagnosed chronic non-communicable diseases (NCDs) in America are accompanied by a grieving process that negatively impacts the mental health of those who suffer from them, therefore, patients need to use coping strategies that help enhance resilience. General objective: To analyze coping and resilience strategies as mediating factors of grief for loss of health in patients with NSTC. Methods: Descriptive correlational study with a quantitative and cross-sectional approach. The study population was made up of patients with NCDs who attended the outpatient service of a Health Center. To obtain the data, three questionnaires were applied: Carver's Abbreviated COPE, Wagnild and Young's Resilience Scale (RS) and the Psychological Responses to Grief Scale for Loss of Health (RPD-PS-38). Results: A statistically significant association is identified between coping strategies and resilience (p = 0.007), in turn, factors such as promises/negotiation and faith/hope are related to a greater capacity to face the challenges of loss of health, and on the other hand, factors such as depression, denial and anger are related to a negative impact on the quality of life of people with NCDs. Conclusions: Individuals who have coping strategies such as promises/negotiation, faith/hope, as well as high levels of resilience, face grief in the face of loss of health with better emotional and relational resources.